(untitled) (EAAE Annual Conference Proceedings, 2023)
Many students describe the work process at the university as chaotic. There are many courses with different topics and many students with interests known or unknown to their peers and professors. All-nighters are still much more than an exception, and often such practices continue even after graduation during work in the office. In the architectural profession, time planning stands out as one of the project planning processes that has a significant impact on the financial outcome of the project. The course intends to acquaint students with PM processes through application and development of awareness of their impact on scheduling and time management.